Pengaruh kinerja lingkungan, media exposure, agresivitas pajak, dan kepemilikan asing terhadap pengungkapan CSR - Fauzimar, Laena Hening; Setyorini, Dhyah (Akuntansi dan Teknologi Informasi, 2025)
Purpose – This study aims to analyze the influence of environmental performance, media exposure, tax aggressiveness, and foreign ownership on Corporate Social Responsibility (CSR) disclosure in energy and raw materials sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Methods – The research was conducted by analyzing secondary data on companies in the energy and raw materials sector with a sample of 24 companies over four (4) years of observation. The data obtained were tested using multiple linear regression analysis. Findings - The results of the study indicate that environmental performance and media exposure have a significant positive effect on CSR disclosure. However, tax aggressiveness and foreign ownership do not. Implications - The findings highlight the importance for companies to improve environmental performance and utilize media exposure as key factors in gaining societal legitimacy and ensuring business sustainability. For stakeholders, the study offers a useful reference in evaluating CSR disclosure quality. Originality - This study simultaneously examines four determinants of CSR disclosure using a sample of energy and raw material companies, thereby extending prior research that focused primarily on the mining sector.